2019
DOI: 10.1097/tp.0000000000002559
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Suboptimal Donor Characteristics on Mortality After Liver Transplantation: A Time-dependent Analysis Comparing HCC With Non-HCC Patients

Abstract: Conception of the project, data analysis, interpretation of results and write up of the manuscript. Mrs Susan Charman: interpretation of results and write up of the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 26 publications
1
42
0
Order By: Relevance
“…Adjustment for differences in recipient characteristics only or for both recipients and donor characteristics had minimal effects on the observed time trends in post‐transplantation outcomes of recipients with or without HCC. Instead, tumour recurrence was identified as the main factor responsible for the consistently poorer long‐term survival among recipients with HCC. Accordingly, improvements in the longer‐term survival of recipients with HCC are more likely to be influenced by changes in the selection of such patients for liver transplantation than by donor‐related factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Adjustment for differences in recipient characteristics only or for both recipients and donor characteristics had minimal effects on the observed time trends in post‐transplantation outcomes of recipients with or without HCC. Instead, tumour recurrence was identified as the main factor responsible for the consistently poorer long‐term survival among recipients with HCC. Accordingly, improvements in the longer‐term survival of recipients with HCC are more likely to be influenced by changes in the selection of such patients for liver transplantation than by donor‐related factors.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, tumour recurrence was identified as the main factor responsible for the consistently poorer long‐term survival among recipients with HCC. Accordingly, improvements in the longer‐term survival of recipients with HCC are more likely to be influenced by changes in the selection of such patients for liver transplantation than by donor‐related factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…( 27 ) The present study found no difference in HCC recurrence rates between the DCD and DBD groups, consistent with recent literature on the topic. ( 11,28 ) The fact that survival was worse in HCC patients at higher risk for recurrence who received a DCD liver but recurrence rates were similar between groups is meaningful and points toward the DCD graft itself as a contributor to the difference in survival. These findings support a “two‐hit” hypothesis where patients who, first, are at high risk for recurrence and, then, receive a DCD liver have particularly poor post‐LT patient and graft survival.…”
Section: Discussionmentioning
confidence: 99%